THE AGILE HUMAN CAPITAL CONCEPT IN FINTECH FOR THE BABY BOOMER GENERATION - Agus Maulana; Muhammad Fauzan; Edi Susanto; Aremu Bashiru; Muhammad Ghalih (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2025)
Financial literacy is an important aspect for students in managing personal finances effectively. This study was conducted at the Universitas Pendidikan Indonesia. The purpose of this study was to determine the level of literacy, perceptions of the importance of financial literacy, and the impact of financial literacy on the financial decision-making of students at the Faculty of Economics and Business Education, Universitas Pendidikan Indonesia. The research method used is a descriptive qualitative method. The data technique used was through a questionnaire involving 100 respondents. The results of the study showed that students at the Faculty of Economics and Business Education, Universitas Pendidikan Indonesia, have a good understanding of financial literacy, with 76% of respondents strongly agreeing that financial literacy is very important in their lives. In addition, students who have good financial literacy tend to be more organized in managing their finances, such as in recording income and expenses. This study provides insight into how financial literacy can help students avoid consumptive behavior and make wise financial decisions. Therefore, it is recommended that universities develop more structured educational programs to improve financial literacy among students.